2020
DOI: 10.3390/ma13235423
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Performance Evaluation of Titanium Dioxide Nanotube-Reinforced Cement Paste

Abstract: Considering the increase in research regarding environmental pollution reduction, the utilization of cementitious material, a commonly used construction material, in photocatalysts has become a desirable research field for the widespread application of photocatalytic degradation technology. Nano-reinforcement technology for cementitious materials has been extensively researched and developed. In this work, as a new and promising reinforcing agent for cementitious materials, the photocatalytic performance of ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
(69 reference statements)
2
11
0
1
Order By: Relevance
“…Moreover, the cement hydration process is influenced not only by the amount of the added additive, but also by its surface to volume ratio. For example, Liu et al [ 134 ] characterized the effect of various TiO 2 powders and nanotubes on the hydration process of cement grout. For this purpose, cement pastes, each containing 1 wt.% of the mass of cement micro-TiO 2 (m-TiO 2 ), nano-TiO 2 (n-TiO 2 ) particles, or TiO 2 (TNT) nanotubes obtained by the hydrothermal method with a BET surface of 196 m 2 /g were used.…”
Section: Results Of Mechanical Properties Of Modified Cement Mortarsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the cement hydration process is influenced not only by the amount of the added additive, but also by its surface to volume ratio. For example, Liu et al [ 134 ] characterized the effect of various TiO 2 powders and nanotubes on the hydration process of cement grout. For this purpose, cement pastes, each containing 1 wt.% of the mass of cement micro-TiO 2 (m-TiO 2 ), nano-TiO 2 (n-TiO 2 ) particles, or TiO 2 (TNT) nanotubes obtained by the hydrothermal method with a BET surface of 196 m 2 /g were used.…”
Section: Results Of Mechanical Properties Of Modified Cement Mortarsmentioning
confidence: 99%
“…Different admixtures may have different effects on cement hydration behavior and microstructure formation due to their different characteristics [ 106 , 134 , 135 ]. Recent studies by Goyal et al [ 105 ] comparing the effects of nano-TiO 2 (NT) and nano-ZnO (NZ) on the hydration behavior of Portland cement have shown that NT accelerates hydration while NZ delays it.…”
Section: Results Of Mechanical Properties Of Modified Cement Mortarsmentioning
confidence: 99%
“…In the past few decades, TiO 2 has been used as a building material for atmospheric NOx removal by exploiting the NOx oxidation mechanism of TiO 2 [ 22 , 23 , 24 , 25 ]. Chen and Poon [ 26 ] provided an overview of the development of photocatalytic construction materials in terms of academic achievements and practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have been conducted to analyze the oxidation mechanism of TiO2 under various experimental conditions [16][17][18][19][20][21]. In the past few decades, TiO2 has been used as a building material for atmospheric NOx removal by exploiting the NOx oxidation mechanism of TiO2 [22][23][24][25]. Chen and Poon [26] provided an overview of the development of photocatalytic construction materials in terms of academic achievements and practical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation